Personality traits and passion for their sport among junior elite athletes - Bauger, L.; Eisemann, M.; Vangberg, H. C. B. (13th FEPSAC European Congress of Sport Psychology, 2011)
The present study aims to investigate the relationship between personality traits, athletic discipline, passion for the sport, performance and self esteem. 139 senior high school students, attending schools for elite level junior athletes completed a test battery comprising Junior Temperament and Character Inventory (J-TCI), Passion scale, Rosenberg self esteem scale (RSES), and World Health Organization`s WHO-5 well-being index. Preliminary results show that athletes competing in team sports score higher on the temperament traits of Novelty seeking and Harm avoidance and on the character traits of Reward dependence, Cooperativeness and Self transcendence than those competing in individual sports. On the other hand, athletes from individual sports score higher on Persistence and Self-directedness.We found a significant difference on personality traits between the different competition levels, (p = .006 Wilks` Lambada = .735).The difference that was significant were harm avoidance, values on this personality trait were reduced for higher competitive participants. Male athletes in our study scored significantly higher on Rosenberg`s self-esteem measure, while female athletes had higher values on the temperament trait reward dependence and the character trait cooperativeness, (p < .05). Further, we found self-esteem positively correlated with harmonious passion whereas harm avoidance correlated negatively with self-esteem. Finally, well-being correlated positively with self-directedness and self-esteem and negatively with harm avoidance. Our results should be useful in guiding both coaches and athletes for optimizing their training.